Pediatric post-tonsillectomy hemorrhage in the setting of post-transplantation immunosuppression. (April 2017) - Quintanilla-Dieck, Lourdes; Chinnadurai, Sivakumar; Wootten, Christopher; Goudy, Steven L.; Virgin, Frank W.
Abstract: Introduction: Long-term immunosuppressants form an integral part of therapy for post-transplantation patients. Immunosuppressants may also have an anticoagulant effect, and little is known about their effects on bleeding risk after adenotonsillectomy. Our objective was to investigate whether there is an increased observed rate of post-tonsillectomy hemorrhage in a population of pediatric patients on long-term immunosuppressants after solid organ transplantation, compared to healthy controls. Methods: This was a retrospective chart review of pediatric patients with a history of renal or heart transplant undergoing adenotonsillectomy at our institution between 2000 and 2014. All patients underwent tonsillectomy with monopolar electrocautery. Retrieved data included perioperative medications, occurrence of post-operative bleeding and associated treatment. For comparison, we obtained a population of age-matched controls with no history of immunosuppression who underwent the same procedure. Results: A total of 34 patients meeting criteria were identified, of which 3 (8.82%) suffered a postoperative bleed. Forty-seven controls were obtained, with a total of 2 (4.26%) postoperative hemorrhages ( p  = 0.65). Two of the post-transplantation patients who bled postoperatively required cauterization in the operating room. None of the controls required surgical treatment. The incidences of postoperative bleeding requiring surgical treatment were 5.88% and 0%, respectively ( p  = 0.17). Conclusion: We failed to demonstrate an increased risk of bleeding after undergoing adenotonsillectomy in our cohort of post-transplantation pediatric patients on chronic immunosuppression. Future research, likely requiring a multi-institutional effort, could stratify by immunosuppressive agent to elucidate bleeding risk with specific medications.